New approach to desensitization in solid organ transplantation-imlifidase - Durlik, Magdalena (Frontiers in Transplantation, 2022)
The IgG-degrading enzyme derived from Streptococcus pyogenes is a recombinant cysteine protease of S. pyogenes produced in Escherichia coli that cleaves all four human subclasses of IgG with strict specificity. The proteolytic activity on IgG molecules prevents the occurrence of IgG-mediated antibody-dependent, cellular cytotoxicity and complement-mediated cytotoxicity, two processes that are critical for antibody rejection. The results from phase II studies demonstrated that desensitization with imlifidase represents a therapeutic strategy that can operationalize desensitization, allowing life-saving transplants from deceased donors (DD) and living donors (LD) to proceed in highly sensitized kidney transplant candidates with low risk of hyperacute rejection. Its action onset is rapid, allowing kidney transplantation from a deceased donor. Disadvantages of imlifidase include a quick reappearance of DSAs, which poses a risk of antibody-mediated rejection, the quick development of anti-Ides antibodies, which rules out repeated use of imlifidase and its IgG-degrading potential, limiting the use of therapeutic antibodies. Imlifdase received conditional approval on 26 August 2020 in the EU for desensitization treatment of highly sensitized adult kidney transplant patients with positive crossmatch against an available deceased donor.